2007
DOI: 10.1007/s11126-007-9042-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a children’s home and community-based services waiver program

Abstract: It would seem that the HCBS program appears to be a clinically and cost-effective method of maintaining children in their community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Studies examining these policies in relation to mental health care for children are limited. Functional, clinical, and access-related outcomes in existing reports appear to be positive (Friesen et al, 2003; Graaf & Snowden, 2018; Ireys et al, 2006; Solhkhah et al, 2007), and a 2013 report from a federal Medicaid Waiver Demonstration project highlighted promising outcomes for these programs:Using a “systems of care” approach, the Demonstration successfully enabled participants to either improve or maintain their functioning status at less than a third of the cost of serving them in an institution . .…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining these policies in relation to mental health care for children are limited. Functional, clinical, and access-related outcomes in existing reports appear to be positive (Friesen et al, 2003; Graaf & Snowden, 2018; Ireys et al, 2006; Solhkhah et al, 2007), and a 2013 report from a federal Medicaid Waiver Demonstration project highlighted promising outcomes for these programs:Using a “systems of care” approach, the Demonstration successfully enabled participants to either improve or maintain their functioning status at less than a third of the cost of serving them in an institution . .…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, it was suggested that IHT may be the preferred approach. However, IHT requires a viable living environment with parents or guardians who are willing to engage in therapy (Solhkhah et al 2007), and this home environment may not be available in some cases. It is uncertain if these fundamental differences in living environments can be controlled statistically.…”
Section: Introductionmentioning
confidence: 99%
“…Limited evaluation exists, however, regarding Medicaid waivers specifically for this population. Findings in a handful of preliminary studies of such HCBS 1915(c) waivers suggest that state adoption expands the array of community-based services available to these youth and their families, allows more families to access intensive mental health care in the community, and has helped keep more youth in their homes (Friesen et al, 2003;Ireys, Pires, & Lee, 2006;Solhkhah, Passman, Lavezzi, Zoffness, & Silva, 2007). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
mentioning
confidence: 99%